An insight into fluorescent transition metal complexes - Chia, Y.Y; Tay, M.G (Dalton Transactions, 2014)
The emission from transition metal complexes is usually produced from triplet excited states. Owing to strong spin–orbit coupling (SOC), the fast conversion of singlet to triplet excited states via intersystem crossing (ISC) is facilitated. Hence, in transition metal complexes, emission from singlet excited states is not favoured. Nevertheless, a number of examples of transition metal complexes that fluoresce with high intensity have been found and some of them were even comprehensively studied. In general, three common photophysical characteristics are used for the identification of fluorescent emission from a transition metal complex: emission lifetimes on the nanosecond scale; a small Stokes shift; and intense emission under aerated conditions. For most of the complexes reviewed here, singlet emission is the result of ligand-based fluorescence, which is the dominant emission process due to poor metal–ligand interactions leading to a small metal contribution in the excited states, and a competitive fluorescence rate constant when compared to the ISC rate constant. In addition to the pure fluorescence from metal complexes, another two types of fluorescent emissions were also reviewed, namely, delayed fluorescence and fluorescence–phosphorescence dual emissions. Both emissions also have their respective unique characteristics, and thus they are discussed in this perspective.